Deﬁniowanie pojęć w miejscowych planach zagospodarowania przestrzennego - Pawłowski, Sławomir (Wydawnictwo Naukowe UAM, 2015)
The subject of this paper is local spatial development plans, and in particular, the glossaries that accompany those plans. The glossaries contain deﬁnitions which, when expanded to cover wider scopes, constitute an essential element of the legislative activity of a local authority, as they consequently directly inﬂuence the surounding spatial order. Many of the deﬁned concepts that have been subject to our analysis are very interesting, but the one which has inspired the research the results of which are presented in this paper is a term ”architectonical dominant”. Already the fact that its meaning must be arbitrarily interpreted due to the fact that the words used to create it are themselves under-deﬁned, means that in consequence every attempt to give the term a concrete meaning (concept) may bring about different results. And yet, clearly, a possibility to introduce certain deﬁnitions means that spatial planning authorities have been granted such discretionary powers to do so. First, the signiﬁcance and the idea of local spatial plans and the scope of independence of local authorities in the shaping of those plans are discussed. Next, the general principles of deﬁning concepts contained in local spatial development plans are presented, followed by an analysis of the relationship between statutory eﬁnitions used in legislative acts and those contained in respective local spatial development plans. Apart from the deﬁnitions contained in the latter, which refer to statutory acts, also those of a stricte law-making character are analysed as the most interesting. The conclusion of the deliberations is a recommendation that deﬁnitions in local spatial development plans should neither be arbitrarily introduced, nor should unnecessarily modify the generally binding provisions of applicable laws. The practice of using different terms to denote the same concept, common among local law-making bodies, is also criticised, especially since these other terms frequently lack clear deﬁnitions.
Deﬁning concepts in local plans of spatial development
Keywords: spatial order; local spatial development plan; deﬁ nitions